Examining the Relationship Between Nursing Students’ Belief in a Just World and Their Attitudes Towards Death - Ulaş Karaahmetoğlu, Gülşen; Durmus Iskender, Mahinur (SAGE Publications, 2022)
The belief in a just world is a mindset that facilitates our ability to cope with life events by fostering a sense of control. Nursing students' beliefs in a just world and their attitudes towards death can influence how they will care for their patients. The intent of this descriptive and cross-sectional study was to examine the relationship between nursing students and their beliefs in a just world and their attitudes towards death. Quantitative data was collected using the Descriptive Characteristics Questionnaire, the Belief in a Just World Scale, and the Attitude towards Death Scale. The sample included 270 participants. It was determined that as nursing students’ beliefs in a just world increased, they developed positive attitudes towards death. It is recommended that discussions on the subject should be included in the education curriculum to increase nursing students' beliefs in a just world and their awareness about death.
Keywords: Cross-Sectional Studies; Attitude of Health Personnel; Surveys and Questionnaires; Humans; Students, Nursing; Curriculum; 4. Education; 3. Good health